HUBUNGAN PENGETAHUAN TERHADAP PERILAKU MENJAGA KESEHATAN GIGI SELAMA MASA PANDEMI - Mulyani, Sri; Azizah, Hudzaifah Alief Fath; Nareswari, Indi; Nafisa, Azka Tazkiyatun; Hanifa, Hasna (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2022)
Background: Oral and dental health is important, especially for school-age children. Factors that can have an impact on the level of dental and oral health are health behaviors that are influenced by knowledge. Objective: To determine the relationship or correlation between knowledge of oral and dental health on the behavior of maintaining dental health in students of Madrasah Ibtidaiah Negeri 6 Ngawi. Methods: This study used a cross sectional study design with a population of 80 students. Sampling using a total sampling technique, namely the number of samples equal to the total population. Data was collected using a questionnaire filled out online. The data that has been obtained will be analyzed with the chi-square test. Results: The study showed that most of the respondents had good knowledge of oral and dental health. Having the behavior of maintaining dental health is in the moderate category. From the results of the analysis, there is a significant relationship between knowledge about oral health and dental behavior in students of Madrasah Ibtidaiah Negeri 6 Ngawi, namely p value 0.016 <0.05. Conclusion: There is a relationship between knowledge about oral health and behavior to maintain dental health.